2008
DOI: 10.1177/008124630803800412
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of Naval Specialists: Their Sense of Coherence and its Relationship with Measures of Personality

Abstract: The occupational demands placed on naval specialists require them to be individuals with high levels of resilience. In this study, I firstly measured the sense of coherence (SoC) of naval specialists, which included 97 divers and 318 submariners, and the results confirmed the high scores hypothesised. Secondly, I explored the relationship between sense of coherence and certain personality traits known to be important for naval specialists, as measured by the 16 Personality Factor Questionnaire (16PF), the IPAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…IJOMEH 2014;27(6) 964 and hyperbaric injury, the low scores are contextually appropriate and support the outcomes of the previous studies [1,7,[10][11][12]17]. It has been suggested that standard deviations > 1.5 above the mean could be used as a cut-off point between clinical and non-clinical scores, to be consistent with the international use of other psychological measures [18].…”
Section: Objective 2: Value Of Entry Stpi Scores To Predict Qualificasupporting
confidence: 76%
See 1 more Smart Citation
“…IJOMEH 2014;27(6) 964 and hyperbaric injury, the low scores are contextually appropriate and support the outcomes of the previous studies [1,7,[10][11][12]17]. It has been suggested that standard deviations > 1.5 above the mean could be used as a cut-off point between clinical and non-clinical scores, to be consistent with the international use of other psychological measures [18].…”
Section: Objective 2: Value Of Entry Stpi Scores To Predict Qualificasupporting
confidence: 76%
“…The above studies concern the civilian (and mostly recreational) diving environment. The United States Navy divers traditionally report lower trait anxiety than norm groups [10], and South African Navy (SAN) divers and submariners on measures of generalized anxiety score lower than or close to general local population means [11]. Trait anxiety has further been associated with injury proneness during military diving training [12], and injured naval trainee divers report higher baseline (i.e., pre-course) trait anxiety scores than the non-injured trainees [13].…”
Section: Introductionmentioning
confidence: 98%
“…Likewise, certain dispositional traits associated with adaptive coping have been described among US Navy (USN) submarine crews, including detachment, propriety, and workaholism (Moes, Johnson, & Lall, 1996), and South African Navy (SAN) submariners, including adventurousness, confidence, group orientation, and precision (Van Wijk & Waters, 2000). Both SAN divers and submariners score high on sense of coherence scales, suggesting a positive dispositional orientation to life (Van Wijk, 2008).…”
Section: Coping In the Context Of Extreme Environmentsmentioning
confidence: 99%
“…Certain dispositional personality traits associated with adaptive coping have been described among military divers, including optimism, adventurousness, confidence, independence, and an internal locus of control (Beckman et al, 1996;Biersner & LaRocco, 1983;Van Wijk, 2008;Van Wijk & Waters, 2001). Likewise, certain dispositional traits associated with adaptive coping have been described among US Navy (USN) submarine crews, including detachment, propriety, and workaholism (Moes, Johnson, & Lall, 1996), and South African Navy (SAN) submariners, including adventurousness, confidence, group orientation, and precision (Van Wijk & Waters, 2000).…”
Section: Coping In the Context Of Extreme Environmentsmentioning
confidence: 99%
“…In confined spaces, the promotion of social cohesion also needs to be balanced with the need for privacy in such environments. SAN submariners are characterized by high resilience (Van Wijk, 2008), and presumably have good self-regulating skills, which might make them dispositionally less demanding of the group's psychological resources. In spite of this, the demands of submarine operations and their associated stresses may require all to draw on the collective psychological resources of the group, to maintain effective coping.…”
Section: Introductionmentioning
confidence: 99%